2011
DOI: 10.1038/icb.2011.17
|View full text |Cite
|
Sign up to set email alerts
|

Rapid death of duck cells infected with influenza: a potential mechanism for host resistance to H5N1

Abstract: Aquatic birds are the natural reservoir for most subtypes of influenza A, and a source of novel viruses with the potential to cause human pandemics, fatal zoonotic disease or devastating epizootics in poultry. It is well recognised that waterfowl typically show few clinical signs following influenza A infection, in contrast, terrestrial poultry such as chickens may develop severe disease with rapid death following infection with highly pathogenic avian influenza. This study examined the cellular response to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 41 publications
2
46
0
Order By: Relevance
“…4C, middle and bottom). Kuchipudi et al reported that duck cells underwent rapid cell death after infection with a minimally pathogenic avian H2N3, classical swine H1N1, and classical highly pathogenic H5N1 viruses, but the chicken cells underwent cell death less frequently (Kuchipudi et al, 2012). It was here observed that dRIG-I protected chicken cells from ZB07-induced apoptosis.…”
Section: Discussionsupporting
confidence: 44%
“…4C, middle and bottom). Kuchipudi et al reported that duck cells underwent rapid cell death after infection with a minimally pathogenic avian H2N3, classical swine H1N1, and classical highly pathogenic H5N1 viruses, but the chicken cells underwent cell death less frequently (Kuchipudi et al, 2012). It was here observed that dRIG-I protected chicken cells from ZB07-induced apoptosis.…”
Section: Discussionsupporting
confidence: 44%
“…and elevated in the lungs of infected ducks compared with the later induction of apoptosis in infected chickens. Rapid cell death was found in an in vitro study were duck embryo fibroblast cells were infected with HPAI H5N1 (Kuchipudi et al, 2011), which may lead to a reduced number of virus-infected cells in ducks. Another study (Vanderven et al, 2012) describes the rapid induction of antiviral genes involved in antiviral defence and other cellular processes in the lung of H5N1 HPAI-infected ducks at 1 d.p.i.…”
Section: Discussionmentioning
confidence: 99%
“…Karpala et al (2011b) reported that MDA-5 levels were up-regulated during HPAI infection in chickens, which could indicate that MDA-5 can functionally compensate for the absence of RIG-I (Liniger et al, 2012). Another explanation for the difference in pathogenesis between ducks and chickens could be that a rapid induction of apoptosis in HPAI-infected ducks may be beneficial to the host, whereas delayed apoptosis in chickens may be an advantage for the virus (Kuchipudi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis (programmed cell death) is another mechanism by which cells restrict viral infection including influenza [67]. However, virus-induced apoptosis causes tissue damage, which is one of the mechanisms of influenza pathogenicity [68].…”
Section: Discussionmentioning
confidence: 99%